Spectral-domain optical coherence tomography findings in polypoidal choroidal vasculopathy - Ghazi, Nicola G. (2012)
Purpose: to report spectral domain optical coherence tomography (SD-OCT) findings in polypoidal choroidal vasculopathy (PCV) Methods: Ten eyes of 10 consecutive patients were diagnosed with PCV based on typical clinical and angiographic findings including indocyanine green angiography. All eyes were also imaged with macular SD-OCT including line scans passing through the polyps. Results: SD-OCT findings included typical and atypical retinal pigment epithelial (RPE) detachments (PED) and subretinal and intraretinal fluid in all eyes. In addition in the areas corresponding to the polyps, well-delineated round-oval, sub-RPE cavities with low to medium reflectivity centrally and hyperreflective borders were noted within the space of an atypical PED. The cavities were adherent to the posterior surface of the detached RPE way above the subjacent Bruch membrane, and the RPE appeared to be draped over them. No retinal or choroidal connections to the cavities were noted. Conclusions: These findings suggest that the polyps in PCV are not located in the inner choroid, but rather in the sub-RPE space, anterior to Bruch membrane. The close proximity of the polyps to the RPE and the configuration of the RPE around the polyps may shed light on the pathogenesis of PCV and may also contribute to the relatively good prognosis of PCV compared to typical choroidal neovascularization.